Transformasi Limbah Minyak Jelantah Menjadi Produk Sabun-Batang di Dukung Digital-Branding Sebagai Upaya Kemandirian Ekonomi - Sari, Rafika; Ramdhania, Khairunnisa Fadhilla; Sari, Ratna; Adhani, Lisa; Khalida, Rakhmi (Journal Of Computer Science Contributions (JUCOSCO), 2024)
Every household produces used cooking oil because the use of cooking oil is one of the primary needs of society.Waste cooking oil if not managed properly will make the environment dirty and can contaminate water and soil.To overcome this problem, innovation is needed in the management of used cooking oil by involving thecommunity so that the waste can be utilized to become recyclable products that can be reused in everyday life andeven become products of economic value that are environmentally friendly. One of the potential wastes of cookingoil is the high content of fatty acids that can be used to make soap. Soap products can be obtained from thehydrolysis reaction of fatty acids with bases (alkali). Therefore, this Community Service (PkM) activity wascarried out to increase the added value of used cooking oil by processing it into bar soap. This PkM activityincludes four stages, namely observation, information transformation, digital literacy and activity evaluation. Thetarget of this service program is housewives (IRT) in Srimukti Village, Bekasi Regency. From the results of asurvey conducted after the training activities, the participants were very satisfied with the ease of obtaininginformation about the implementation of the training, the training material in the form of processing used cookingoil waste and improving digital-branding skills which were considered very necessary for residents and the waythe instructor delivered material that was easy to understand.